Effect of Pilates on Sleep Quality: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Chen, Zehua; Ye, Xiangling; Shen, Zhen; Chen, Guoqian; Chen, Weijian; He, Ting; Xu, Xuemeng (Frontiers in Neurology, 2020)
Abstract Objective: Pilates exercise is increasingly used to improve sleep quality, but relevant evidence remains unclear. We aimed to estimate the effect of pilates on sleep quality. Methods: Searches were conducted in five databases for articles published until December 10, 2019. Two reviews screened the articles and extract data from each included study. Meta-analysis was performed to evaluate the effect of pilates on sleep quality assessed with the Pittsburgh Sleep Quality Index (PSQI). Results: Six randomized controlled trials (RCTs) comprising 477 participants were included according to the inclusion and exclusion criteria in the study. All included studies reported the positive effects of pilates on sleep quality. Pilates group (PG) significantly lowered the PSQI total score (MD =-3.60, 95%CI: [-5.41, -1.78), P = 0.0001, I2 = 97%) compared to non-exercising control group (CG). However, there was no statistically significant difference between two groups in use of sleeping medication (MD =-0.33, 95%CI: [-0.73, -0.06), P = 0.10, I2 = 68%). Compared to CG, we found that there was no significantly reduction in the PSQI total score for healthy participants over 40 years old (reported in four studies) (MD =-3.73, 95%CI: [-7.89, 0.42] , P = 0.08, I2 = 98%) and postmenopausal women (reported in two studies) (MD =-5.55, 95%CI: [-13.98, -2.89] , P = 0.20, I2 = 98%). Conclusions: Overall, pilates improved sleep quality but had no significant effect on the use of sleeping medication. However, for healthy individuals over 40 years old and postmenopausal women, pilates showed no satisfactory results and the positive effect was not significant. Well‐designed and large‐scale RCTs are needed in the future.